2016
DOI: 10.5665/sleep.6218
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Quality in Relation to Autonomic Nervous System Measures: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Study Objectives: Short sleep duration and poor sleep quality are associated with adverse cardiovascular outcomes. Potential pathophysiological mechanisms include sleep-associated alterations in the autonomic nervous system. The objective of this study was to examine the associations of shorter sleep duration and poorer sleep quality with markers of autonomic tone: heart rate (HR), high-frequency HR variability (HF-HRV) and salivary amylase. Methods: Cross-sectional analysis of data from actigraphy-based measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 61 publications
1
83
1
5
Order By: Relevance
“…The findings from Myllymäki's and Castro-Diehl's [28,29] studies may help us to understand our results and to identify a significant relationship between sleep quality and HR max. These studies lead us to understand that changes in sleep patterns cause a significant loss in the autonomic response, which affects the behavior of these variables in stress condition.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The findings from Myllymäki's and Castro-Diehl's [28,29] studies may help us to understand our results and to identify a significant relationship between sleep quality and HR max. These studies lead us to understand that changes in sleep patterns cause a significant loss in the autonomic response, which affects the behavior of these variables in stress condition.…”
Section: Discussionmentioning
confidence: 81%
“…Recent study performed by Castro-Diehl and colleagues [29] verified the associations between shorter sleep duration (less than six hours per night), poor sleep quality and markers of autonomic nervous system, as heart rate (HR) and high-frequency HR variability (HF-HRV). The authors observed that subjects who slept less than six hours had higher heart rate and had lower baseline HF-HRV when compared to subjects that slept seven hour or more, proving the relationship between short sleep duration and autonomic markers.…”
Section: Discussionmentioning
confidence: 92%
“…18 Kualitas tidur yang buruk dapat mengubah hormon kortisol dan perubahan sistem saraf otonom dengan aktivasi peningkatan simpatis atau penurunan parasimpatis sehingga terjadi peningkatan tekanan darah. 25,26 Penelitian di Pekanbaru menunjukkan bahwa IMT/U memiliki hubungan yang signifikan dengan tekanan darah. Berdasarkan penelitian tersebut, diprediksikan setiap kenaikan IMT/U sebesar 1 kg/m 2 maka nilai tekanan darah sistol dan diastol akan meningkat masing-masing sebesar 2,339 mmHg dan 0,979 mmHg.…”
Section: Pembahasanunclassified
“…Недостаток сна изменяет сердечно-сосудистые параметры, увеличивает симпатическую активность, индуцирует воспалительные процессы во многих тканях (мозг, жировая ткань, печень, селезенка), включая сердце и сосудистый эндотелий [39]. У испытуемых, спавших <6 ч в сут., по сравнению с теми, кто спал ≥7 ч, отмечались нарушения вегетативной регуляции сердца (измерялись по индексу вариабельности сердечного ритма), гипертонус симпатической системы и понижение влияния парасимпатической нервной системы [40].…”
unclassified